Artificial intelligence in justice: Protocols for the submission and assessment of AI-generated digital evidence - Aguilar Cabrera, Denis (2024)
The integration of artificial intelligence (AI) into criminal law marks a significant advancement with broad implications for the management of digital evidence in judicial proceedings. AI provides tools that can enhance the efficiency, quality, and transparency of criminal justice, while also posing ethical and legal challenges that need to be addressed with caution. In fact, the incorporation of algorithms and AI systems can contribute to establishing more objective and consistent criteria in decisionmaking. It is crucial to thoroughly analyze the ethical and legal implications when integrating AI into criminal processes, ensuring the protection of fundamental rights and respect for the presumption of innocence. The safeguarding of individual rights and the responsibility of automated systems are critical elements that must be considered when establishing a clear regulatory framework governing the use of artificial intelligence in criminal proceedings. Moreover, AI algorithms must adhere to basic principles such as in dubio pro reo, and judges must have the ability to depart from AI recommendations if they adequately justify their decisions, maintaining a balance between automation and judicial discretion. It is essential to understand that AI is not intended to replace the role of the human judge but rather to complement it as a support tool to ensure effective and equitable justice in the digital age.